Born inversion for broadband ultrasonic monitoring of cancer treatment - Karbeyaz, B; Miller, E; Cleveland, R; Roy, R (AIP Publishing, 2006)
One barrier to developing High Intensity Focused Ultrasound (HIFU) methods for clinical use is monitoring the progress of the treatment by non‐invasive imaging techniques. In this work, we propose the use of ultrasound‐based imaging techniques to characterize the geometric structure of the HIFU lesion. To obtain quantitatively accurate reconstructions of the HIFU anomaly, one could invert for the acoustic properties on a densely sampled grid of voxels. However, the computational size of the problem makes traditional pixel based inversion methods impractical. Hence, we exploit the fact that HIFU results in approximately ellipsoidal lesions in which sound speed and attenuation are altered from their nominal values. By employing shape‐based methods it is only necessary to estimate a small number of parameters to describe the geometry of the lesion. The details of this nonlinear inversion method are provided and its performance and robustness are demonstrated using broadband ultrasound backscatter data obtained with a commercial ultrasound scanner and a tissue phantom containing a HIFU‐like lesion.